Microbial Corrosion Behavior of L245 Pipeline Steel in the Presence of Iron-Oxidizing Bacteria and Shewanella algae - Fanghui Zhu; Yiyang Liu; Chunsheng Wu; Kai Li; Yingshuai Hu; Wei Liu; Shuzhen Yu; Mingxing Li; Xiaohuan Dong; Haobo Yu (Microorganisms, 2025)
Microbiologically influenced corrosion (MIC) poses significant challenges in oilfield water injection environments, leading to substantial socioeconomic losses. L245 steel, a low-alloy steel widely used in oil and gas pipelines due to its excellent mechanical properties and cost-effectiveness, remains highly vulnerable to MIC during long-term service. This study uses surface characterization and electrochemical techniques to investigate the corrosion behavior of L245 pipeline steel under short-cycle conditions in a symbiotic environment of iron-oxidizing bacteria (IOB) and Shewanella algae (S. algae). Key findings revealed that localized corrosion of L245 steel was markedly exacerbated under coexisting IOB and S. algae conditions compared to monoculture systems. However, the uniform corrosion rate under symbiosis fell between the rates observed in the individual IOB and S. algae systems. Mechanistically, the enhanced corrosion under symbiotic conditions was attributed to the synergistic electron transfer interaction: IOB exploited electron carriers secreted by S. algae during extracellular electron transfer (EET), which amplified the microbial consortium’s capacity to harvest electrons from the steel substrate. These results emphasize the critical role of interspecies electron exchange in accelerating localized degradation of carbon steel under complex microbial consortia, with implications for developing targeted mitigation strategies in industrial pipelines exposed to similar microbiological environments.